Peran Standarisasi halal Dalam Membangun Daya Tarik Konsumen yang Sangat Kuat Terhadap Suatu Produk di Dalam Industri Pasar Global - Faiqotul Himmah; Romi Faslah (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This inquiry investigates the pivotal function of halal standardization in cultivating robust consumer appeal within the global market. Amidst escalating consumer awareness in the digital age, halal certification transcends mere religious observance, evolving into a critical determinant in purchasing decisions. This study aims to elucidate how adherence to Islamic dietary and ethical guidelines, spanning raw materials, production processes, and distribution, instills a sense of security and preference among both Muslim and non-Muslim consumers. Furthermore, the halal label inherently communicates attributes of quality, hygiene, and assured production, thereby expanding market reach beyond the conventional Muslim demographic. Utilizing a qualitative library research approach, this paper synthesizes existing scholarly literature to explain how halal standards can become a key factor in attracting consumer attention and influencing global purchasing behavior, ultimately contributing to a more responsible consumption landscape and fostering increased product demand worldwide.